Comparative analysis between FPA and COCOMO techniques for software cost estimation - Ali Moftah, Abu Baker (2014)
Software cost estimation is the process of predicting the effort required to develop a software system. The basic inputs for the software cost estimation are programs, size and set of cost drivers, while the output is effort in the form of person-month and cost. In this thesis, Function Point Analysis (FPA) and Constructive Cost Model (COCOMO) have been used to estimate software project cost of two case studies. They are Web-Based Dog’s Diseases Diagnosis System (WBDDDS) and Sugar Bun Online Bakery System (SBOBSE). By using FPA, it was shown that for the WBDDDS, the person-month was 12.506 with the total cost of USD65,031.2 were estimated. While using COCOMO, it was shown that 16.286 persons-month with the total cost of USD 84,687.2 were estimated. However, for the SBDBSE, by using FPA, 19.62 persons-month with the total cost of USD102,024 were estimated. It also shown that 19.354 persons-month with the total cost of USD100,640.8 were estimated by using COCOMO. In conclusion, there are no best techniques to estimat 3 e cost for a project. It al 77$ l depends on the parameters of a system